Dental topography and the diet of Homo naledi. Issue 118 (May 2018) - Berthaume, Michael A.; Delezene, Lucas K.; Kupczik, Kornelius
Abstract: Though late Middle Pleistocene in age, Homo naledi is characterized by a mosaic of Australopithecus -like (e.g., curved fingers, small brains) and Homo -like (e.g., elongated lower limbs) traits, which may suggest it occupied a unique ecological niche. Ecological reconstructions inform on niche occupation, and are particularly successful when using dental material. Tooth shape (via dental topography) and size were quantified for four groups of South African Plio-Pleistocene hominins (specimens of Australopithecus africanus, Paranthropus robustus, H. naledi, and Homo sp.) on relatively unworn M2 s to investigate possible ecological differentiation in H. naledi relative to taxa with similar known geographical ranges. H. naledi has smaller, but higher-crowned and more wear resistant teeth than Australopithecus and Paranthropus . These results are found in both lightly and moderately worn teeth. There are no differences in tooth sharpness or complexity. Combined with the high level of dental chipping in H. naledi, this suggests that, relative to Australopithecus and Paranthropus, H. naledi consumed foods with similar fracture mechanics properties but more abrasive particles (e.g., dust, grit), which could be due to a dietary and/or environmental shift(s). The same factors that differentiate H. naledi from Australopithecus and Paranthropus may also differentiate it from Homo sp., which geologically predates it, in the same way. Compared to the great apes, all hominins have sharper teeth, indicating they consumed foods requiring higher shear forces during mastication. Despite some anatomical similarities, H. naledi likely occupied a distinct ecological niche from the South African hominins that predate it.